Compatibility as guiding principle for ergonomics work design and preventive occupational health and safety; Kompatibilität, Leitlinie für ergonomische Arbeitsgestaltung und präventiven Arbeitsschutz - Helmut Strasser (Zeitschrift für Arbeitswissenschaft, 2021)
Mutual adaptation and inter-changeability of system elements are very important prerequisites for machines, technical devices and products. Similar to that technical compatibility which can be achieved by standards and regulations, optimum design of human-oriented workplaces or a~man-machine system cannot be attained without, e.g., a~compatible arrangement of connected displays and controls. Over and above those stimulus/response relations, all technical elements and interfaces have to be designed in such a~way that they do not exceed human capacity in order to optimize human well-being and overall system performance. Compatibility between the properties of the human organism on the one hand, and the adaptable technical components of a~work system on the other hand, offers a~great potential of preventive measures. Examples of ergonomically designed working tools show that compatibility is capable of reducing the prevalence of occupational diseases and repetitive strain injuries as well as leading to lower physiological cost in such a~way that the same output results from a~lower demand of human resources or even a~higher performance will be attained. Compatibility also supports the quick perception and transmission of information in a~man-machine system, and as a~result of lower requirements for decoding during information processing, spare mental capacity may enhance occupational safety. In the field of software, compatibility also helps to avoid psychological frustration. All in all, the center core competency, which reflects the major significant function of the ergonomist in work design, consists in determining the compatibility of human capacity and planned or existing demands of work. In order to provide efficient working tools and working conditions as well as to be successful in occupational health and safety, ergonomics and industrial engineering in the future are expected to pay more attention to the rules of compatibility. Applied in an appropriate way, these rules may convince people that ergonomics can be a~powerful means for reducing prevalence of occupational diseases and complaints, and has a~positive effect on overall system performance. Besides presenting examples of work design according to the principle of compatibility, also methods will be shown which enable the assessment of the ergonomic quality of hand-held tools and computer input devices.
Keywords: 650; Compatibility; Ergonomic work design; Preventive occupational health; Physiological cost; Kompatibilität; Ergonomische Arbeitsgestaltung; Präventiver Arbeitsschutz; Physiologische Kosten